(untitled) (Signifiances (Signifying), 2017)
Paraguay’s two co-official languages, Spanish and Guarani, have experienced close, extended contact. This has contributed to the emergence of dialectal variants known as « Jopara », in which units from both languages alternate. In this paper, we put forth the view that the alternation, in Jopara Spanish, of the discourse markers ko, ningo (both of Guarani origin), and luego (from Spanish) is the manifestation of a new epistemic subsystem based on the reanalysis of « biomechanically embodied » cognitive operators (Bottineau 2012), which are incorporated into a semiological network that transcends this semantic field alone. Our corpus is composed of excerpts from the online discussion forums of the newspaper Hoy, which belongs to the Multimedia group located in Asunción (Paraguay).